2015
DOI: 10.1038/nmat4173
|View full text |Cite
|
Sign up to set email alerts
|

Template-free nanosized faujasite-type zeolites

Abstract: Nanosized faujasite (FAU) crystals have great potential as catalysts or adsorbents to more efficiently process present and forthcoming synthetic and renewable feedstocks in oil refining, petrochemistry and fine chemistry. Here, we report the rational design of template-free nanosized FAU zeolites with exceptional properties, including extremely small crystallites (10-15 nm) with a narrow particle size distribution, high crystalline yields (above 80%), micropore volumes (0.30 cm(3) g(-1)) comparable to their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
302
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(314 citation statements)
references
References 28 publications
10
302
0
2
Order By: Relevance
“…Therefore, large efforts have been made in order to improve the catalyst performance. This has been realized by reduction of the intracrystalline diffusion path length in the following possible approaches: synthesis of zeolites with extra-large pores [15][16][17][18][19][20], direct synthesis of zeolite nanocrystals [21][22][23][24][25][26][27], by exfoliating layered zeolites [28,29], and by introducing mesopores in the microporous materials through templating strategies [14,30,31] or demetallation processes [4,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, large efforts have been made in order to improve the catalyst performance. This has been realized by reduction of the intracrystalline diffusion path length in the following possible approaches: synthesis of zeolites with extra-large pores [15][16][17][18][19][20], direct synthesis of zeolite nanocrystals [21][22][23][24][25][26][27], by exfoliating layered zeolites [28,29], and by introducing mesopores in the microporous materials through templating strategies [14,30,31] or demetallation processes [4,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Nano-sized zeolites are crucial industrial catalysts and adsorbent because of less diffusion limitations compared to micrometer-sized ones [5]. Synthesis of nanoparticles of ZSM-5, EMT and FAU has been previously reported [6][7][8]. Mordenite (MOR) is a zeolite with 12 MR and 8 MR channels that have c direction elongation and run one-dimensionally along the c-axis; therefore, MOR crystals with ultrashort c-direction can decrease the diffusion limitations [9].…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization process at low temperature decreases the kinetic polymerization of silicate and aluminate to obtain highly uniform precursor particles and limits Ostwald ripening [8]. In addition, the high concentration of organic template or SDA could provide abundant crystal nuclei, which lead to small crystallites with a narrow particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…However, processing of these inorganic materials is difficult and costly. [10,11] Over the last couple of years, much progress has also been made on the development of synthetic organic nanostructured materials with smaller features by using the self-assembly properties of LC behavior. Comparison of the FT-IR spectra of the individual components with the complex showed that a hydrogenbonded complex was formed (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%